2002
DOI: 10.1046/j.0022-0477.2001.01255.x
|View full text |Cite
|
Sign up to set email alerts
|

An ELISA for recombinant Lepidoglyphus destructor, Lep d 2, and the monitoring of exposure to dust mite allergens in farming households

Abstract: When assessing mite allergen exposure in rural homes, not only the Der p 1, Der f 1 and Der 2 allergens, but also the Lep d 2 allergen should be taken into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Exposure to mite allergens has been recognised worldwide as an important risk factor for development of sensitisation and allergic disease [23]. The significant source of exposure to house dust mite allergens is mattresses [24], which is in line with the current findings and our recent report where we have shown that farmers' mattresses contain high levels of mite allergens [10]. Our patient was a part-time, small-scale farmer from a relatively humid area in southeastern Sweden.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Exposure to mite allergens has been recognised worldwide as an important risk factor for development of sensitisation and allergic disease [23]. The significant source of exposure to house dust mite allergens is mattresses [24], which is in line with the current findings and our recent report where we have shown that farmers' mattresses contain high levels of mite allergens [10]. Our patient was a part-time, small-scale farmer from a relatively humid area in southeastern Sweden.…”
Section: Discussionsupporting
confidence: 90%
“…A value of >0.35 kU/l is regarded as positive. Mite allergens levels (Dermatophagoides pteronyssinus, Der p1, Dermatophagoides farinae, Der f1 and Lepidoglyphus destructor, Lep d2) were measured in a dust sample collected from the bed mattress by suctioning 1 m 2 for 2 min with a vacuum cleaner using a separate filter bag (Medeca AB, Uppsala, Sweden) and prepared and stored as described earlier [10]. Values ≥55 ng/g are regarded as positive for Der p/f1 and ≥90 ng/g for Lep d2.…”
Section: Methodsmentioning
confidence: 99%
“…These were analyzed using quantitative polymerase chain reaction (qPCR) techniques [7]. Allergen levels were determined using two-site sandwich ELISA for house dust mite (Der p1, Der f1), cat (Fel d1), dog (Can f1) while horse allergen (Equ cx) was measured using monoclonal antibodies [8] [9]. Due to the lack of established guidelines, data has been reported in quartiles and schools having indoor concentrations within the upper quartile were considered as having elevated levels of the particular microbiological or allergen contaminant.…”
Section: Microbiology and Allergensmentioning
confidence: 99%
“…Attention should be paid to proper cleaning practices and protection against mites. The allergens from the storage mite Lepidoglyphus destrutor, such as Lep d 1 and Lep d 2, have been purified and characterized, and a method for measuring allergens in dust samples has been developed (24)(25)(26)(27)(28). Furthermore, we need new commercial methods for measuring storage mite allergens in order to study comprehensively the possible role of mites in sensitizing laboratory animal workers.…”
Section: Discussionmentioning
confidence: 99%